Personnel management policies and practices and the inclusion of individuals with disabilities: a quantitative study - Silva, Alice Gerlane Cardoso da; Helal, Diogo Henrique (Revista de Administração da UFSM, 2019)
This study analyzes how the policies and practices of personnel management directed at individuals with disabilities in João Pessoa, PB, Brazil, are configured concerning their insertion and inclusion into the labor market. For such, a quantitative research of descriptive character was conducted using the survey method. The research was developed with individuals, with and without disabilities, who worked and resided in João Pessoa. In total, 90 individuals partook of the study, 45 of which presented disability while the other 45 presented none. The questionnaire was applied in person and made available on the internet by means of the Google Docs system. Data analysis was done using SPSS, consisting of a factorial and descriptive analyses, analysis of variance (ANOVA) and non-parametric tests Kruskal-Wallis and median. The results demonstrated that, despite the individuals with disabilities perceiving an evolution of personnel management policies and practices applied by the organizations regarding the manner of capturing, accepting and coexisting with individuals with disabilities, they are not yet enough to assure their effective inclusion in the labor market.